Microfluidics-based devices: New tools for studying cancer and cancer stem cell migration - Huang, Yu (American Institute of Physics, 2011)
Cell movement is highly sensitive to stimuli from the extracellular matrix and media. Receptors on the plasma membrane in cells can activate signal transduction pathways that change the mechanical behavior of a cell by reorganizing motion-related organelles. Cancer cells change their migration mechanisms in response to different environments more robustly than noncancer cells. Therefore, therapeutic approaches to immobilize cancer cells via inhibition of the related signal transduction pathways rely on a better understanding of cell migration mechanisms. In recent years, engineers have been working with biologists to apply microfluidics technology to study cell migration. As opposed to conventional cultures on dishes, microfluidics deals with the manipulation of fluids that are geometrically constrained to a submillimeter scale. Such small scales offer a number of advantages including cost effectiveness, low consumption of reagents, high sensitivity, high spatiotemporal resolution, and laminar flow. Therefore, microfluidics has a potential as a new platform to study cell migration. In this review, we summarized recent progress on the application of microfluidics in cancer and other cell migration researches. These studies have enhanced our understanding of cell migration and cancer invasion as well as their responses to subtle variations in their microenvironment. We hope that this review will serve as an interdisciplinary guidance for both biologists and engineers as they further develop the microfluidic toolbox toward applications in cancer research.